Adoption Internet of Things on Islamic Boarding School: A Systematic Literature Review - Lutfiyah, Konita; Maarif, Mohamad Syamsul; Asnawi, Yudha Heryawan; Arsyianti, Laily Dwi (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Internet of Things in Islamic boarding schools can become an embedded system that aims to expand the use of continuously connected internet connectivity. The importance of IoT modernization in Islamic education is because it eliminates skills gaps and lags. A brief comprehensive review is needed to help researchers and practitioners understand the adoption of internet of things on Islamic boarding school.Purpose: This study aims to analyze and classify the literature on Internet of Things on Islamic Boarding school. Design/methodology by conducting literature studies published between 2017-2023 in the journal listed in the Journal Citation ReportDesign/methodology/approach: This research is analyzed according to a systematic literature review approach involving interpretation-based assessments of research methodologies and critical findings in the study. Findings/Result: The direction of this research is expected in the future to have implications for academics and practitioners. Internet of Things (IoT) brings the potential for significant disruption in various sectors, including education and places such as Islamic boarding schools.Conclusion: Some of the problems and importance of IoT disruption for Islamic boarding schools include limited human resources where Islamic boarding schools may have limited resources, both in terms of finances and technological infrastructure. Implementing IoT technology requires initial investment and maintenance which can be an additional burden.Originality/value (State of the art): IoT in Islamic boarding schools can become an embedded system that aims to expand the use of continuously connected internet connectivity. The importance of IoT modernization in Islamic education will eliminates skills gaps and lags in the education areas. Keywords: internet of things, islamic boarding school, connectivity, systematic literature review